Research on the Efficiency and Economic Impact of Energy-Saving Transformation of Residential Buildings in Different Climatic Regions of China - Qibo Liu; Wei Feng (Advances in Materials Science and Engineering)
In China, the transformation of existing buildings is confronted with various problems in aspects ranging from technology to policy and even to economic efficiency, which restrains the pace of existing building transformation. Aiming at these conditions, a building model is established with simulation software in the research herein to deeply analyze the energy-saving effect of building envelope transformation in different climatic regions and its economic efficiency based on regional and national policies. The research results show that any single technology is difficult to completely satisfy the requirements of current energy efficiency standards, and technical measures should be taken according to different climatic regions. For the northern heating area, the building envelope transformation must be carried out simultaneously with the transformation of heat metering. Policy formulation and fund determination for the energy-saving transformation of existing buildings in China should be more flexible based on transformation effect and rely more on social and commercial forces rather than solely on the promotion of government.